Sarcoidosis as an Autoimmune Disease - Starshinova, Anna A.; Malkova, Anna M.; Basantsova, Natalia Y.; Zinchenko, Yulia S.; Kudryavtsev, Igor V.; Ershov, Gennadiy A.; Soprun, Lidia A.; Mayevskaya, Vera A.; Churilov, Leonid P.; Yablonskiy, Piotr K. (Frontiers in Immunology, 2020)
Despite the large number of performed studies, the etiology and pathogenesis of sarcoidosis still remains unknown. Most researchers allude to the possible autoimmune or immune-mediated genesis of the disease. This review attempts an integral analysis of currently available information suggesting an autoimmune genesis of sarcoidosis and is divided into four categories: the evaluation of clinical signs described both in patients with sarcoidosis and “classic” autoimmune diseases, the role of triggering factors in the development of sarcoidosis, the presence of immunogenic susceptibility in the development of the disease; the analysis of cellular and humoral immune responses in sarcoidosis. Studying the etiology and pathogenesis of sarcoidosis will improve diagnostic procedures as well as the prognosis and patients’ quality of life.